2018
DOI: 10.1080/14616734.2018.1499211
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Attachment Disorder in maltreated young children in foster care

Abstract: Reactive attachment disorder (RAD) is one of the least researched and most poorly understood psychiatric disorders. Very little is known about the prevalence and stability of RAD symptoms over time. Until recently it has been difficult to investigate RAD due to limited tools for informing a diagnosis. Utilising a newly developed observational tool along with the Disturbances of Attachment Interview. this short-term prospective longitudinal study explored RAD symptoms in maltreated young children in Scotland (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Even though the adverse history of postinstitutionalized foster and adopted children shows similarities with family-reared, never-institutionalized foster children, examinations of the relation between improved caregiving quality after placement in the latter group are scarce. M. Bruce et al (2019) did describe reduced attachment disorder symptoms after children had been placed in a foster family, but these results were limited to inhibited social behavior characterizing RAD and did not include symptoms of DSED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the adverse history of postinstitutionalized foster and adopted children shows similarities with family-reared, never-institutionalized foster children, examinations of the relation between improved caregiving quality after placement in the latter group are scarce. M. Bruce et al (2019) did describe reduced attachment disorder symptoms after children had been placed in a foster family, but these results were limited to inhibited social behavior characterizing RAD and did not include symptoms of DSED.…”
Section: Discussionmentioning
confidence: 99%
“…Bruce et al (2019) did describe reduced attachment disorder symptoms after children had been placed in a foster family, but these results were limited to inhibited social behavior characterizing RAD and did not include symptoms of DSED. Moreover, of these studies only Van den Dries et al (2012) and Garvin et al (2012) used the Emotional Availability Scales (Biringen et al, 1998) as an instrument to specifically measure parental sensitivity, whereas the other studies presumed that the adoption or foster placement in itself indicated an improvement in caregiving quality (M. Bruce et al, 2019; Rutter et al, 2007; Zeanah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on clinical data collected in the course of providing research‐informed specialist care for maltreated foster and adopted children and their caregivers. Due to differences in diagnostic instruments, procedures, and populations, the relatively low in‐clinic prevalence of DSED and absence of RAD cannot be directly compared to the usually higher clinical prevalence rates of RAD or DSED (e.g., Bruce et al., ; Kay, Green, & Sharma, ; Zeanah et al., ) or rates of inhibited attachment behavior or disinhibited social engagement behavior (e.g., Jonkman et al., ; Scheper et al., ). For one, RAD symptoms were simply recorded as present or absent on the basis of a clinical interview, whereas in the original versions of the DAI and IFI, subclinical levels of these symptoms may also be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to date, none of the studies of children adopted from Romanian orphanages have documented a diagnostic case of RAD after a period of time living in an adoptive home (Zeanah & Gleason, ). However, some cases of persistent observer‐rated and caregiver‐reported RAD behavior in nonpermanent foster care have been reported (Bruce et al., ; Jonkman et al., ). Third, the indiscriminate sociability of DSED may persist even after the child is placed in a stable and responsive caregiving environment (Chisholm, ; Rutter et al., ).…”
Section: Introductionmentioning
confidence: 99%